ANALISA PERBANDINGAN BIAYA DAN WAKTU PELAKSANAAN DINDING PENAHAN TANAH SECANT PILE DENGAN DIAPHRAGM WALL PADA PROYEK REVITALISASI TAMAN ISMAIL MARZUKI - Silvianengsih, Silvianengsih; Misriani, Merley; Natalia, Monika; Ihdini, Gheniy; Fadila, Jamilatul (Jurusan Teknik Sipil Universitas Bangka Belitung, 2023)
The construction of a basement for parking lots requires a soil retaining wall structure that can withstand its own load and the load around it and must be safe against sliding, rolling and collapse. The choice of soil retaining wall type is an important decision in development projects because it affects the cost, quality and time of implementation. Secant pile soil retaining wall is a type of soil retaining wall using the method of arranging concrete poles that are arranged intersectingly to withstand soil thrust. Diaphragm wall is a type of soil retaining wall that uses reinforced concrete to withstand the lateral force of the soil made by filling concrete that has been made first and filled with bentonite slurry as a stabilizer of the excavated wall, then filled with concrete after the reinforcement cage is installed. Later it will be compared with the diaphragm wall in terms of cost and implementation time. The data needed in this analysis are shop drawing secant pile, technical specifications, unit price of work, and detailed geotechnical design engineering. From the results of the study, it was found that the cost of secant pile work amounted to Rp. 24,560,508,232.00 with an implementation time of 214 working days. As for the diaphragm wall, a work fee of Rp.30,059,442,748.00 was obtained with an implementation time of 246 working days. The application of secant pile is 18.29% cheaper and 32 days faster than diaphragm wall.